Recent progress in the utilization of pea protein as an emulsifier for food applications - Burger, Travis G.; Zhang, Yue (Trends in food science & technology, 2019)
There is an increasing movement within the food industry to find consumer friendly plant protein ingredients to replace those from animal sources. Pea (Pisum sativum L.) protein has been extensively studied because it provides good nutritional properties, functionality, is readily available, and has low allergenicity. The focus of this review is a summary of the current progress in understanding and characterizing the use of pea protein as an emulsifier. The emulsification properties of pea protein are described in comparison to other protein emulsifiers. The impact of origin, processing, and environmental conditions like temperature, pH, and ionic strength is discussed. The physicochemical properties of the protein, such as solubility, surface charge, hydrophobicity, and composition are also covered, along with current methods to improve functionality. One of the most valuable functional properties of pea protein is emulsification, which can be affected by its origin, isolation method, and the environmental or processing conditions (pH, ionic strength, and temperature). The physicochemical properties including solubility, surface charge/hydrophobicity, and interfacial properties have been examined to evaluate their emulsifying functionality. While several methods such as complexation, glycosylation, and enzymatic hydrolysis have been developed to further improve the pea protein, there remains a gap between the functionality of laboratory and commercially prepared products. There is an opportunity to increase the functionality of pea protein by understanding and closing this gap. •The emulsification properties of pea protein were described in comparison to other protein emulsifiers.•The emulsification and stabilization mechanisms of pea protein were discussed.•Factors affecting the emulsifying properties of pea protein were described.•Emulsifying properties of pea protein were improved by complexation, glycosylation, and enzymatic hydrolysis.•There remains a gap between the functionality of laboratory and commercially prepared pea protein.